Bowen–Walters expansiveness for semigroups of linear operators. (18th June 2023) - LEE, J.; MORALES, C. A.
Abstract: We define positively expansive semigroups of linear operators on Banach spaces . We characterize these semigroups in terms of the point spectrum of the infinitesimal generator. In particular, we prove that a positively expansive semigroup is neither uniformly bounded nor equicontinuous. We apply our results to the Lasota equation.